INVESTIGATION OF THE INCIDENCE OF BREAST CANCER AMONG THE FEMALE PATIENTS OF JAMHURIAT HOSPITAL IN KABUL, A CROSS-SECTIONAL STUDY 2023 (World Bulletin of Public Health, 2024)
Breast cancer (BC) is one of the malignant tumors of the breast tissue, which is more common in women. This disease is more prevalent with age. The purpose of this study is to investigate the prevalence of BC among women who are referred to the oncology department of Jamhuriat Hospital in Kabul.
Keywords: Breast cancer; incidence; Kabul